Termination challenges in child psychotherapy - Gil, Eliana; Crenshaw, David A. (The Guilford Press, 2016)
Ending therapy in an appropriate and meaningful way is especially important in work with children and adolescents, yet the topic is often overlooked in clinical training. From leading child clinicians, this much-needed book examines the termination process, both for brief and longer-term encounters, and offers practical guidance illustrated with vivid case material. Tools are provided for helping children and families understand termination and work through associated feelings of loss and grief. Challenges in creating positive endings to therapy with children who have experienced trauma an.